On the search for conditions for production process optimization - Szerszunowicz, Małgorzata (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2014)
The experimental design methodology mainly deals with the estimation of a usually unknown response surface function. An important problem in the field of design of experiments is to determine the number of experimental trials, taking into account certain limitations resulting from the nature of the manufacturing process. The experimental design methodology also includes – as if a separate section – methods of searching for conditions for the optimization of processes and the optimal design of experiments. The aim of this paper is to present a method of searching for conditions for the optimization of manufacturing process results. The proposed method uses non-classical statistical methods and is presented for selected empirical data.
Mathematical Economics, 2014, Nr 10 (17), s. 91-102
Keywords: design of experiments; response surface function; optimal design